Extracellular Vesicle: An Emerging Mediator of Intercellular Crosstalk in Lung Inflammation and Injury - Lee, Heedoo; Abston, Eric; Zhang, Duo; Rai, Ashish; Jin, Yang (Frontiers in Immunology, 2018)
Inflammatory lung responses are one of the characterized features in the pathogenesis of many lung diseases including acute respiratory distress syndrome (ARDS) and chronic obstructive pulmonary disease (COPD). Alveolar macrophages (AMs) and alveolar epithelial cells are the first line of host defense and innate immunity. Due to their central roles in both the initiation and resolution of inflammatory lung responses, AMs constantly communicate with other lung cells including the alveolar epithelial cells. In the past, emerging evidence suggests that extracellular vesicles (EVs) play an essential role in cell-cell crosstalk. In this review, we will discuss the recent findings on the intercellular communications between lung epithelial cells and alveolar macrophages, via EV-mediated signal transfer.